Articulating reproductive justice through reparative justice: case studies of abortion in Great Britain and South Africa. Issue 5 (4th May 2017) - Macleod, Catriona Ida; Beynon-Jones, Siân; Toerien, Merran
Abstract: Public health and rights-based approaches to abortion advocacy are well established. Feminists are, however, increasingly using a broader framework of 'reproductive justice', which considers the intersecting conditions that serve to enhance or hinder women's reproductive freedoms, including their capacities to decide about the outcome of their pregnancies. Nonetheless, reproductive justice approaches to abortion are, conceptually, relatively under-developed. We introduce a reparative justice approach as a method of further articulating the concept of reproductive justice. We first explain how this approach can be used to conceptualise safe, accessible and supportive abortion as a key element of reproductive justice in relation to the injustice of unwanted or unsupportable pregnancies. Using Ernesto Verdeja's critical theory of reparative justice and case studies of two countries (South Africa and Great Britain) where abortion is legal, we show how such an approach enables an analysis of reproductive justice within the specificities of particular contexts. We argue that both the rights-based legal framework adopted in South Africa and the medicalised approach of British law have, in practice, limited reparative justice in these contexts. We discuss the implications of reparative justice for abortion advocacy.